AKTIVITI MISIONARI: ANTARA KEHENDAK PERLEMBAGAAN, PERINTAH BIBLE DAN REAKSI MUSLIM DI MALAYSIA - Abdul Rahman, Mohamad Zaidi (Jurnal Syariah, 2019)
This article will evaluate the status of religious propagation, which is embedded in Article 11(4) of the Malaysian Constitution. Historically, such provision can be traced back to its historical roots in the Malay states from the time of the British administration. Subsequently, it was extended into the Malaysian Constitution as stated under Article 11(4). This provision literally guarantees the rights of every person to propagate his/her religion but with a certain restrictive element excluding Muslims from being the target of other religions. However, such provision could be observed as being contrary to the preaching spirit of the Bible to all people including Muslims. Therefore, it is interesting to know what position the Christians in Malaysia take on an ethical question â€œwho should be obeyed between God and man?â€ The answer may be critical, particularly concerning Christian-Muslim affairs in the Malaysian context.